Biomarkers of Complement and Platelet Activation are not correlated with the One or Twenty-Four Hours Corrected Count Increments in Prophylactically Platelet Transfused Hematological Patients: a Prospective Cohort Study. (3rd April 2022) - Åkesson, Alexander; Ljungkvist, Marcus; Martin, Myriam; Blom, Anna M.; Klintman, Jenny; Schött, Ulf; Zetterberg, Eva; Kander, Thomas
Abstract: Platelet transfusion refractoriness is a serious clinical concern that complicates the management of thrombocytopenic patients. Previous studies have suggested a potential role for both complement and platelet activation based on in vitro analyses of platelet concentrates. In this study, the post-transfusion platelet response, as indicated by the corrected count increment at 1 and 24 h after prophylactic platelet transfusions, respectively, was correlated with the 1 h post-transfusion Δconcentration (1 h post-transfusion – pretransfusion) of complement and platelet activation biomarkers. The study was registered as a clinical trial at ClinicalTrials.gov (identifier: NCT02601131) and patients were recruited during inpatient care in the hematological department. Soluble terminal complement complexes, soluble P-selectin and soluble CD40 ligand were analyzed. Confirmed alloimmunized patients were excluded. Included subjects were either given platelet transfusions (n = 43) and categorized into four clinical study groups or included in a non-transfused control group (n = 10). In total, 54 transfusions were included. No transfusion-mediated complement activation was observed. The transfusions were associated with a significant increase in the concentration of soluble P-selectin ( p < .001), primarily corresponding to the passive infusion of soluble P-selectin-containing plasma residuals. The Δconcentration of soluble P-selectin was, however, not significantly correlated with the corrected count increments. Thus, significant correlations between biomarkers of complement and platelet activation and the post-transfusion platelet response could not be demonstrated in this study.